Scenarios on food security, environments and adaptation in the Great Lakes region, Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 25-27 June, decision-makers and researchers from across the East African Great Lakes region met in Entebbe, Uganda to discuss what the future might hold in terms of development, agriculture and environmental change, and what this may mean for national and regional policies. This meeting was organized by the UNEP World Conservation Monitoring Centre, the Albertine Rift Conservation Society and the CGIAR Research Program on Climate Change, Agriculture and Food Security Program (CCAFS), using research to discuss important policy questions in the face of an uncertain future.